Analisis Pemodelan Curah Hujan - Limpasan dengan Metode NAM dan Sacramento pada Sub DAS Cikeruh, Jawa Barat - Ika Sari Damayanthi Sebayang (FORUM MEKANIKA, 2020)
Floods in the Cikeruh watershed often occur every year during the rainy season. In addition to the rainy season there are several other factors that influence, such as slope, land height, soil type and land use. With this study, it is expected to be able to provide information on the location of floods in the Cisadane watershed with the aim of helping to make decisions in carrying out actions, prevention, reducing the risk of flooding. The data used in this study are secondary data, namely the average annual rainfall data from 13 stations, soil type data, DEMNAS data (National Elevation Data Model), RBI maps with a scale of 1: 25,000 and Cisadane watershed maps. The method used in this study uses the scoring and overlay method where each parameter used to analyze the level of flood vulnerability in the Cisadane watershed is rainfall, slope, elevation, soil type, distance to the river (river buffer), and use land that is given a value and weight according to the classification of the level of vulnerability. Processing data in this study using ArcGis 10.2.2 software. The results of the study resulted in a map of flood vulnerability levels in the Cisadane watershed which provided information on the distribution of locations prone to flooding. Around 76.77% or 116,178,559 ha of the Cisadane watershed area is prone to flooding with a very high vulnerability to the level of medium vulnerability that is spread from upstream to downstream